Genome-Wide Identification, In Silico Analysis and Expression Profiling of SWEET Gene Family in Loquat (Eriobotrya japonica Lindl.) - Binqi Li; Muhammad Moaaz Ali; Tianxin Guo; Shariq Mahmood Alam; Shaista Gull; Junaid Iftikhar; Ahmed Fathy Yousef; Walid F. A. Mosa; Faxing Chen (Agriculture, 2022)
SWEETs (sugars will eventually be exported transporters) have various physiological and biochemical roles in plant growth, including pollen development, seed nourishment, nectar secretion, and longer-distance sugar transportation. The SWEET genes were identified in various plant species, but they have not yet been thoroughly characterized. Here, we discovered 21 putative SWEET genes from the Eriobotrya japonica Lindl. genome. For further elucidation, comprehensive bioinformatics analysis was utilized to determine the physicochemical properties, gene organization, conserved motifs, cis-regulatory elements, gene duplication, and phylogenetic relationships of EjSWEET genes. Most of the SWEET proteins were predicted to be located on the plasma membrane or vacuole. Gene organization and motif analysis showed that the numbers of exons and motifs in each gene ranged strikingly, between 5 and 6 and between 5 and 8, respectively. Synteny analysis showed that the tandem or segmental duplication played a dynamic role in the evolution of SWEET genes in loquat. Likewise, we analyzed the expression patterns of EjSWEET genes in the root, stem, leaf, flower, and fruit of loquat. Some genes exhibited varying expression in loquat tissues, indicating their potential roles in plant development. The relative expression levels of EjSWEET1, EjSWEET3, and EjSWEET16 were noticeably higher in ripened fruits, suggesting their possible role in the transportation and unloading of sugars in fruits. The present study provides initial genome-wide identification and characterization of the SWEET gene family in loquat and lays the foundation for their further functional analysis.